Classification of speech dysfluencies using LPC based parameterization techniques - Hariharan, Muthusamy; Lim, Sin Chee; Ooi, Chia Ai; Sazali, Yaacob, Prof. Dr. (Springer Science+Business Media, LLC., 2011)
Link to publisher's homepage at http://www.springerlink.com/